In-Vitro Effect of Lawsonia Inermis L. (Henna) Leave Extract on Lycopersicon Esculentum Var. (Tomato) Phytopathogenic Bacteria Ralstonia Solanacearum (Smith) - S, Abubakar; A. Y, Dawakiji; I, Bala (The Asia Journal of Applied Microbiology, 2015)
Lycopersicon esculentum (Tomatoes), is one of the most important vegetable fruits worldwide which constitute commercially and nutritionally indispensible food commodity. Ralstonia solanacearum is a relevant and widespread Phytopathogenic bacterium that causes a wilt disease which deadly affects this economically important crop. Antibacterial activity of Lawsonia inermis leaves were evaluated using three fractions of extract namely; methanolic, chloroform and aqueous against this plant pathogenic bacterium (R. solanacearum) in-vitro. Prior to antibacterial assay, the extract fractions were subjected to preliminary phytochemical screening, which revealed the present of alkaloids, terpenoides and saponins in all, while methanolic extract shows the additional flavonoids, tannins, amino acid, triterpenoids and reducing sugar, the chloroform extract showed additional anthraquinone. Nevertheless, the aqueous extract shows the additional triterpenoids, steroids and reducing sugar. Among the three fractions the methanolic extract proved to be the promising extract for management/treatment of tomato wilt caused by R. solanacearum. All the methanolic extract concentrations (1000, 2000, 3000 and 4000 μg/ml respectively) showed effects on the test organism. The (SPSS) software was used to analyse the significant differences between each concentrations, using one way Analysis of variance (ANOVA) at critical value (p≥0.05).